2020
DOI: 10.3126/ijasbt.v8i4.33667
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Artemisia annua L. Flavonoids, Artemisinin and Its Derivatives as Potential Drugs Against Novel Coronavirus (SARS –nCoV) as Revealed by In-Silico Studies

Abstract: Coronavirus-induced COVID-19, a highly contagious respiratory illness first originated from Wuhan city of Hubei province, China, and has affected 235 countries across the globe. The COVID-19 is mainly transmitted by the droplets of an infected person when they cough, sneeze, or exhale. Currently, there are no specific drugs licensed for the effective treatment or prevention of COVID-19 and the treatment is mainly focused on controlling symptoms. Identification of small bioactive plant molecules that specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…AD-MET (absorption, distribution, metabolism, excretion and toxicity) analysis of artemisinin showed that it was non-cytotoxic, had good aqueous solubility and a good permeability through the blood-brain barrier with a promising therapeutic potential. Furthermore, molecular docking studies revealed that artemisinin bound to all four proteins and in some cases displayed better binding modes than hydroxychloroquine [85][86][87][88][89]. Thus, ARTs could serve as best leads for further drug development process for SARS-CoV-2 infection.…”
Section: Anti-viralmentioning
confidence: 99%
See 1 more Smart Citation
“…AD-MET (absorption, distribution, metabolism, excretion and toxicity) analysis of artemisinin showed that it was non-cytotoxic, had good aqueous solubility and a good permeability through the blood-brain barrier with a promising therapeutic potential. Furthermore, molecular docking studies revealed that artemisinin bound to all four proteins and in some cases displayed better binding modes than hydroxychloroquine [85][86][87][88][89]. Thus, ARTs could serve as best leads for further drug development process for SARS-CoV-2 infection.…”
Section: Anti-viralmentioning
confidence: 99%
“…Owing to their potent anti-inflammatory, immunoregulatory and antiviral properties, ARTs are being pursued for their activity against SARS-CoV-2 infection. Researchers used in silico approaches to investigate if artemisinin or its derivatives could physically bind any of the COVID-19 target proteins including SARS-CoV-2 spike glycoprotein, spike ectodomain structural protein, the main protease of the virus (M Pro ) or spike receptor-binding domain, thereby preventing SARS-CoV-2 from binding to the host receptor ACE2 [83][84][85][86][87][88][89]. AD-MET (absorption, distribution, metabolism, excretion and toxicity) analysis of artemisinin showed that it was non-cytotoxic, had good aqueous solubility and a good permeability through the blood-brain barrier with a promising therapeutic potential.…”
Section: Anti-viralmentioning
confidence: 99%
“…Several studies have demonstrated the effects of various natural bioactive compounds/secondary metabolites in the therapeutic world. (Pandey et al, 2011;Rai et al, 2012;Arora and Pandey-Rai, 2012;Pandey and Pandey-Rai, 2014;Arora et al, 2017;Pandey-Rai, et al, 2018;Goswami et al, 2019, Rai et al, 2020aRai et al, 2020b;Apoorva et al, 2021Rai et al, 2022;. Recently, the beneficial effects of papaya in curing dengue fever along with homeostatic properties have been also reported.…”
Section: Research Articlementioning
confidence: 99%
“…Artemisinin and its derivatives present in the leaf of A. Annua are known as potential antimalarial due to their high efficiency and mainly for the downregulation of T&B cell activation, thus inhibiting the production of antibodies [53]. Another study states that corticosteroids reduce mortality in patients with severe COVID-19 and remdesivir can reduce the need for mechanical ventilation but has no effect on mortality.…”
Section: Other Potential Therapies Against Covid-19mentioning
confidence: 99%